Are recent protection strategies sufficient for maintaining diverse freshwater benthic diatom assemblages? - Viktória B-Béres (Elsevier, 2021)
Even though microscopic algae play pivotal role in the healthy functioning of freshwater ecosystems, recent water protection strategies rarely consider them and primarily focus on macroscopic organisms. Here, we studied the effect of protection level and utilization type of lowland standing waters on the composition and diversity of benthic diatom assemblages and on the diatom-based ecological status of waters. We hypothesized that (i) protected waters will sustain more diverse diatom assemblages and better ecological quality than not protected ones. We also hypothesized that (ii) the increase in number of utilization will affect negatively on biodiversity and on ecological quality. Clear taxonomic differences were revealed only in protected and not utilized waters while trait composition in protected waters was independent from the utilization type. Neither biodiversity nor ecological status of waters were influenced by protection level. The increase in number of utilization types, however, significantly decreased functional richness. Although high biodiversity of algae can effectively buffer the negative effects of climate change and anthropogenic impact, recent protection strategies are insufficient to support it.